2019
DOI: 10.1016/j.jde.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Measure-theoretic mean equicontinuity and bounded complexity

Abstract: Let (X, B, µ, T ) be a measure preserving system. We say that a function f ∈ L 2 (X, µ) is µ-mean equicontinuous if for any ε > 0 there is k ∈ N and measurable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
(34 reference statements)
2
8
0
Order By: Relevance
“…It is well known that the set of all almost periodic functions, denoted by H ap , is spanned by the set of eigenfunctions. Following this line, also inspired by the study of bounded complexity functions in [32,28] (will be introduced in Subsection 6.3), Yu [63] showed that Theorem 4.12 holds even without the assumption of ergodicity. 63]).…”
Section: 2mentioning
confidence: 97%
See 3 more Smart Citations
“…It is well known that the set of all almost periodic functions, denoted by H ap , is spanned by the set of eigenfunctions. Following this line, also inspired by the study of bounded complexity functions in [32,28] (will be introduced in Subsection 6.3), Yu [63] showed that Theorem 4.12 holds even without the assumption of ergodicity. 63]).…”
Section: 2mentioning
confidence: 97%
“…We have the corresponding dichotomy property. The measure-functional version of mean equicontinuity was implied in [59] and explicitly stated in [18] (or see [63]), which will have value in the study of discrete spectrum (see Section 4). The opposite side is referred to [18].…”
Section: Mean Equicontinuous If and Only If It Is Weyl Mean Equicontimentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, this may go back to [19] via scaled entropy and even [18] by Vershik. Different from the one by Katok, in [1] Ferenczi characterized an ergodic invariant measure with discrete spectrum via measure-theoretic complexity using names of a partition and the Hamming distance (we remark that this kind of measure-theoretic complexity was also discussed in [10]), which was extended recently to non-ergodic case by Yu in [23].…”
mentioning
confidence: 96%